1978
DOI: 10.1080/00913847.1978.11710680
|View full text |Cite
|
Sign up to set email alerts
|

The Stress of Coaching

Abstract: Like many other professions, coaching precipitates psychophysiological stress. Moreover, the authors found that there may be considerable stress on the coach of any sport, not just the major ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In addition, it has been found that coaches' HR responds to specific features of competition such as type and importance of contest. 14,15 Together these studies provide consistent evidence that coach's experience average HR during games/competitions is greater and certain aspects of a competition may accelerate the HR response from baseline game HR.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, it has been found that coaches' HR responds to specific features of competition such as type and importance of contest. 14,15 Together these studies provide consistent evidence that coach's experience average HR during games/competitions is greater and certain aspects of a competition may accelerate the HR response from baseline game HR.…”
Section: Introductionmentioning
confidence: 69%
“…12 Psychophysiological stress is defined as increased psychological and physiological arousal caused by a reaction to perceived threats and demands, and HR has been used to measure this because it is a tightly controlled index of arousal. 13 McCafferty et al 14 examined the HR response of coaches working in various sports, such as swimming, water polo and volleyball, and identified an increase in HR in response to competition. In addition, it has been found that coaches' HR responds to specific features of competition such as type and importance of contest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the many stressors that coaches may face during competitions, stressors are triggered from other demands as well [12]. For example, a study in which high school principals identified the origin of pressures on their coaches found that significant sources of perceived pressure were derived from attempting to meet external standards of excellence; dealing with boosters, fans, parents; coaching high visibility teams; and the internal pressure that coaches place upon themselves [7].…”
Section: Introductionmentioning
confidence: 99%